CRIMES OF PHYSICAL DOMESTIC VIOLENCE AND NEGLIGENCE IN THE HOUSEHOLD - Rinawati, Inten; Mardani; Saefullah (JILPR Journal Indonesia Law and Policy Review, 2024)
Study This aim For do study to influencing variables? happen violence in House stairs (domestic violence) in family , that is form violence physical and neglect . Additionally , research? this is also purposeful For know action preventing and dealing with domestic violence carried out by husbands to wife , as Decision South Jakarta District Court Number 995/ Pid.Sus /2021/PN Jak.Sel . and Verdict South Jakarta District Court Number 130/ Pid.Sus /2022/PN Bks. Second decision the made with objective For discuss domestic violence problems . Specifically, the South Jakarta District Court and the South Jakarta District Court are the research locations. Both courts are in the South Jakarta area. The data collection process was carried out using several research methodologies, namely library research and field research. Primary data collection can be done by conducting interviews with relevant sources. Apart from that, secondary data was also obtained in the form of papers, books and research reports which were directly related to the topic of domestic violence in the form of physical violence and neglect in the household. This data was collected as additional primary data. To uncover the root causes of domestic violence in the form of physical violence and neglect in families in the South Jakarta and Bekasi City areas, the data obtained was then analyzed descriptively and qualitatively. This is done to find out what actions can be taken to reduce the impact of domestic violence. Based on the research results, the main factors that cause domestic violence crimes committed by husbands against their wives are internal factors, especially those related to the personality characteristics (temperament) of the perpetrator. In conditions that trigger uncontrolled anger, such as lack of communication and intense jealousy, these characteristics make it easier for individuals to commit criminal acts. This is because they are more easily affected by these events. It should be noted that education and economic factors are one of the external factors that cause domestic violence. To overcome the problem of criminal acts of domestic violence committed by husbands against wives in South Jakarta, it is necessary to carry out preventive efforts such as instilling moral values from an early age, preventive efforts such as increasing awareness of laws and regulations. , and repressive efforts such as taking action against perpetrators of criminal acts of domestic violence (KDRT).